Flavonas, lignanas e terpeno de Piper umbellata (Piperaceae) - Baldoqui, Debora Cristina [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Kato, Massuo J.; Marques, Márcia O. M. (Sociedade Brasileira de Química, 2009)
The phytochemical investigation of Piper umbellata leaves yielded nine compounds including one terpenoid glucoside, five flavones (vitexin 2-O-β-glucopyranoside, apigenin 8-C-β-D-glucopyranoside,orientin 8-C-β-D-glucopyranoside,5-hydroxy-7,3',4'-trimethoxy-flavone and velutin), two lignans (sesamin e dihydrocubebin) and 4-nerolidylcathecol. Excepting 4-nerolidylcathecol, all compounds have not been described from this species yet.
Flavones, lignans and terpene from Piper umbellata (Piperaceae)
Keywords: Piper umbellata; Potomorphe umbellata; constitutive metabolites